Nonlinear effect of elastic vortexlike motion on the dynamic stress state of solids; Physical Review E; Vol. 93, iss. 5 - Shilko E. V. Evgeny Viktorovich; Grinyaev Yu. V. Yury Vasiljevich; Popov M. Mikhail; Popov V. L. Valentin Leonidovich; Psakhie S. G. Sergey Grigorievich (2016, 2016)
Title screen